Aspergillus fumigatus as an agent of cutaneous aspergillosis in immunocompetent patient: A rare case - Trisniartami Setyaningrum; Karina Dyahtantri Pratiwi (PAGEPress Publications, 2019)
Cutaneous aspergillosis occurs relatively less frequent and therefore remains poorly characterized. Previous reports have described cutaneous aspergillosis as primary or secondary infection. Primary cutaneous aspergillosis usually involves sites of skin injury, at or near intravenous access catheter sites, at sites of traumatic inoculation, and at sites associated with occlusive dressings, burns, or surgery. Primary cutaneous aspergillosis almost always seen in immunocompromised patients and the skin involvement occurs due to hematogenous dissemination from a primary focus or contiguous spread from underlying infected tissues. This is a rare case of an-56-years-old-immunocompetence man with chief complaint of wound and swelling at left leg since 1 year ago that worsen in last 2 months. He got a history of scalded by hot water at his left leg 1 year ago and became swollen with multiple wound on its surface. Examination on regio pedis sinistra there is tumor with verrucous surface 10 cm in diameter, hard with multiple uneven edge ulcer 5 cm in diameter and hyperpigmentation macule unsharply marginated arround. Potassium hydroxide examination showed conidiophores dichotomously branching and septated hyphae that suitable with Aspergillosis sp. From cultures there is velvety-dark-green growth. The microscope findings from the culture specimen showed conidophore, metula, vesicle, phialde, and chains of pigmented conidia that suitable with Aspergillus fumigatus. Blood culture examination showed no growth of fungi. HIV rapid test negative results obtained. Patients treated with Itraconazole 2 x 200 mg for 12 weeks and obtained satisfactory result.